Literatur Review: TEKNOLOGI dalam DOKUMENTASI BANGUNAN PUSAKA - Istiana Adianti; Laretna T. Adishakti; Dwita Hadi Rahmi (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2021)
Heritage buildings are assets for a city. Heirlooms are relics of the past, where the work has historical value, ideas that are useful for further human sustainability. According to the 2013 Heritage City Preservation Charter, inventory and documentation are instruments for structuring and preserving heritage cities. This writing examines the role of digital documentation in heritage buildings with a literature review study. Synthesize articles published from 2017 to 2020, with the appropriate number of articles being 5 pieces. All of the dominant articles raised issues regarding the diversity of heritage building documentation, both digital and manual. This diversity has the potential to increase the accuracy of the identification of heritage buildings. The findings from the synthesized articles create models or schemes to increase the effectiveness of these digital documents in addition to complementing existing documents. The potential for the existence of digital documentation as the beginning of the management of the library building is open to carrying out many activities to improve digital documentation and collaborate with it.